Implementation of Green Human Resource Management to Support Sustainability at Pesona Batik Jombang MSMEs - Titan Meida; Lailatus Sa'adah; Akhmad Taqiyuddin (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
Purpose – Batik MSMEs face increasing demands to adopt environmentally sustainable practices while maintaining business performance. Although Pesona Batik Jombang has implemented several environmentally friendly production activities, the integration of Green Human Resource Management (GHRM) into its human resource practices remain unclear. This study aims to analyze the implementation of GHRM and its role in supporting sustainability at Pesona Batik Jombang MSMEs. Design/methodology/approach – This study employed a descriptive qualitative approach. Data were collected through semi structured interviews, observations, and documentation involving two key informants, namely the business owner and one employee. Data were analyzed using data reduction, data display, and conclusion drawing techniques. Finding/Results – The findings reveal that GHRM implementation at Pesona Batik Jombang remains largely informal and has not been integrated into formal human resource policies. Green Training and Development and Green Employee Relations have been implemented through environmental awareness activities and employee involvement in environmentally friendly practices. However, Green Recruitment, Green Performance Management, and Green Compensation have not been formally implemented due to the absence of environmental criteria and performance-based reward systems. Originality/Value – These practices contribute to sustainability through environmentally responsible production processes and employee participation in environmental management. The study highlights the need for more structured GHRM policies to strengthen sustainability in batik MSMEs.